Effect of exposure to solar radiation on physiological parameters and decline estimation of milk production by crossbred cows (Holstein x Gir) in the southern Piauí State, Brazil - Dias e Silva, Tairon Pannunzio; Sousa Júnior, Severino Cavalcante; Oliveira, Ravy Guerra de; Santos, Karina Rodrigues dos (Comunicata Scientiae, 2012)
This work aimed to evaluate and correlate the thermoregulatory characteristics of crossbredcows (Holstein x Gir) submitted to three different periods of exposure to solar radiation with somemeteorological variables and their effects on milk production. Were twelve lactating cows dividedinto three groups consisting of four animals each, all of the third lactation, up to five years of ageand approximately 50 days of lactation, submitted to different periods of exposure to solar radiation.Milk production per cow in kilograms was recorded in two daily milkings. The respiratory rate (RR),heart rate (RR), rectal temperature (RT) and the decline in milk production (DPL) obtained bythe difference between the weights of the morning and afternoon milkings per cow during theexperiment were collected four times a week in May and June 2011. The results revealed that thetemperature and humidity index (THI) for cows exposed to two hours of solar radiation was higherthan values considered critical for lactating cattle. The group presented three upper critical valuesfor all thermoregulatory characteristics of animals when compared with groups one and two.The thermoregulatory characteristics of animals of groups two and three groups were positivelycorrelated with the decline in milk production and differently with meteorological variables.